LINGUISTIC PECULARITIES OF REALISATION OF PERSUASIVE STRATEGIES IN MOTIVATIONAL TED TALKS SPEECHES - Лопатюк, Наталія; Якимчук, Віра (Видавництво та друкарня Чернівецького національного університету, 2021)
The paper presents the analysis of linguistic means of realization of persuasive strategies in motivational Ted Talks speeches. Nowadays, the popularity of Ted Talks gradually increases due to the variety of meticulously organized speeches presented to the view of society since the moment of TED’s creation. Millions of people from all around the world visit the online TED platform daily in search of inspiration, motivation and knowledge from various spheres. The object of our scientific research is the persuasive strategies in motivational Ted Talks speeches. The relevance of the study is determined by the need to identify and study the mechanisms of verbal realization of persuasive strategies in rhetorical and media discourse, as persuasion in discourse is one of the current problems of modern linguistics. The subject of the research is verbal means of realization of persuasive strategies in the discursive space of Ted Talks speeches. In the research the following methods have been used: the methods of analysis and deduction; the method of pragmatic analysis, the method of contextual analysis, and the descriptive method. The data of the research has been withdrawn from the transcripts of motivational Ted Talks speeches. The scientific novelty of the results obtained is in singling out the peculiarities of persuasive strategies realization in Ted Talks media discourse and working out the typology of persuasive strategies. The study is based on the three persuasive strategies outlined by the principle of rhetoric: ethos, logos, and pathos. Together, they support efficient persuasion and present the tools to effectively connect with the audience; know their interests, prejudices and expectations. Ethos is a persuasive strategy that allows an orator to establish their authority to speak on the subject, logos is categorized as a tool for implementing a logical argument into the speech to prove its point and pathos is a speaker’s attempt to influence the audience emotionally. The results prove that all three of those rhetorical persuasive strategies are frequently used by Ted Talks presenters in their motivational speeches. The appeals to credibility, logic and emotions are the key features implemented in the discursive space of Ted Talks as the necessary elements of persuasion.
ЛІНГВІСТИЧНІ ОСОБЛИВОСТІ РЕАЛІЗАЦІЇ ПЕРСУАЗИВНИХ СТРАТЕГІЙ В МОТИВАЦІЙНИХ ПРОМОВАХ СПІКЕРІВ TED TALKS
ЛІНГВІСТИЧНІ ОСОБЛИВОСТІ РЕАЛІЗАЦІЇ ПЕРСУАЗИВНИХ СТРАТЕГІЙ В МОТИВАЦІЙНИХ ПРОМОВАХ СПІКЕРІВ TED TALKS
Ця стаття присвячена аналізу лінгвістичних засобів реалізації персуазивних стратегій у мотиваційних промовах спікерів Ted Talks. У зв’язку з великою варіативністю тем організованих виступів, представлених суспільству з моменту створення TED, популярність онлайн платформи зростає. Мільйони людей з усього світу щодня відвідують TED у пошуках натхнення, мотивації та знань з різноманітних сфер людської діяльності. Актуальність дослідження визначається необхідністю виявлення та вивчення механізмів вербальної реалізації персуазивних стратегій у медійному дискурсі. Об'єктом дослідження є персуазивні стратегії в мотиваційних промовах Ted Talks. Предметом дослідження є вербальні засоби реалізації персуазивних стратегій в дискурсивному просторі промов Ted Talks. У дослідженні були використані такі методи: аналіз та дедукція, прагматичний аналіз, контекстуальний аналіз, описовий метод. Матеріал дослідження дібрано методом суцільної вибірки з транскриптів мотиваційних промов спікерів Ted Talks. Наукова новизна отриманих результатів полягає у висвітленні особливостей реалізації персуазивних стратегій у медіапросторі Ted Talks, створенні типології перcуазивних стратегій та демонстрації практичного застосування у лінгвістичних дослідженнях. Наукова праця базується на трьох риторичних персуазивних стратегіях риторики: етосі, логосі та пафосі. Разом вони слугують засобами ефективного переконування та є інструментами продуктивного спілкування з аудиторією; знання їх інтересів, упереджень та очікувань. Етосом називають персуазивну стратегію, яка дозволяє оратору проявити свій авторитет для можливості висловлювання на тему його промови. Логос визначають як інструмент впровадження логічного аргументу в промову для доведення свого переконання. Пафос – це спроба оратора емоційно вплинути на аудиторію. Результати доводять, що зазначені риторичні персуазивні стратегії часто використовуються спікерами Ted Talks у мотиваційних промовах. Звернення до довіри, логіки та емоцій є основними функціями, що реалізуються в дискурсному просторі TED Talks як одні з найнеобхідніших елементів персуазивного впливу.
Keywords: persuasive strategies; ethos; pathos; logos; motivational speeches; Ted Talks